2017
DOI: 10.1016/j.trb.2017.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental diagrams of airport surface traffic: Models and applications

Abstract: This paper reveals and explores the flow characteristics of airport surface network on both mesoscopic and macroscopic levels. We propose an efficient modeling approach based on the cell transmission model for simulating the spatio-temporal evolution of flow and congestion on taxiway and apron networks. The existence of link-based fundamental diagram that expresses the functional relationship between link density and flow is demonstrated using empirical data collected in Guangzhou Baiyun airport. The proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…In order to reduce fuel consumption and exhaust emissions during taxiing on the airport surface, push-back control strategy [11,12], taxiing trajectory and speed profile optimizations [13,14], and improvement of taxiing mode (e.g., single-engine taxiing, operational tow-outs, and electric taxiing) [15,16] have been comprehensively investigated. During climb and descent, especially in high-density terminal airspace, prior research has focused more on how to make full use of runway capacity, while minimizing noise, total fuel consumption, emissions, and delays [17][18][19], and put forward operating concepts and operating procedures such as Continuous Climbing Operation (CCO) [20], Continuous Descending Operation (CDO) [21], Point Merge (PM) [22], etc.…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce fuel consumption and exhaust emissions during taxiing on the airport surface, push-back control strategy [11,12], taxiing trajectory and speed profile optimizations [13,14], and improvement of taxiing mode (e.g., single-engine taxiing, operational tow-outs, and electric taxiing) [15,16] have been comprehensively investigated. During climb and descent, especially in high-density terminal airspace, prior research has focused more on how to make full use of runway capacity, while minimizing noise, total fuel consumption, emissions, and delays [17][18][19], and put forward operating concepts and operating procedures such as Continuous Climbing Operation (CCO) [20], Continuous Descending Operation (CDO) [21], Point Merge (PM) [22], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Studies at the airport of Duesseldorf have shown that a constant speed does not exist: taxiing speed can differ and even speed drops can be seen. One mesoscopic model based on cell transmission [10,11] is the model of Yang et al [12] using empirical data of Guangzhou Baiyun International Airport (China). Although this model discribes the dynamic of airplanes on a high level it is not applicable to the airport of Duesseldorf due to the need of unexceptional uni-directional taxiways and traveling direction for links between taxiways.…”
Section: Cellular Automata For Airplane Trafficmentioning
confidence: 99%
“…In 2017, passenger throughput in China exceeded 1.1 billion, or a 12.9% increase from the previous year, with total aircraft operations across airports reaching 102.49 million nationwide. With the fast-paced growth of air traffic, the Chinese civilian airspace-both near terminals and en route-is under increasing stress, with flight delays a common phenomenon at many locations in the system [7,8]. In response, the Civil Aviation Administration of China (CAAC) has introduced a series of new regulations on flight delays.…”
Section: Introductionmentioning
confidence: 99%